2022
DOI: 10.1007/s10840-022-01157-5
|View full text |Cite|
|
Sign up to set email alerts
|

Fluoroless left atrial access for radiofrequency and cryoballoon ablations using a novel radiofrequency transseptal wire

Abstract: Purpose Conventional catheter ablation for atrial fibrillation requires fluoroscopy, which has inherent risks of radiation exposure to patients and medical staff. Optimization of fluoroscopy parameters and use of three-dimensional electroanatomic mapping (EAM) and intracardiac echocardiography (ICE) have helped to reduce radiation exposure; however, despite growing evidence, there are still concerns about safety and added procedure time associated with fluoroless procedures, particularly in left-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…By eliminating the RF needle and additional sheath exchange, time to transseptal puncture from femoral access was 34% (10.8 min) faster using the VersaCross steerable system compared to the standard workflow (Figure 3B). The transseptal puncture times in our study are comparable to those seen in previous fluoroless transseptal punctures [11,15], and fluoroscopy-guided transseptal puncture [10,16] using RF wire or RF needle.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…By eliminating the RF needle and additional sheath exchange, time to transseptal puncture from femoral access was 34% (10.8 min) faster using the VersaCross steerable system compared to the standard workflow (Figure 3B). The transseptal puncture times in our study are comparable to those seen in previous fluoroless transseptal punctures [11,15], and fluoroscopy-guided transseptal puncture [10,16] using RF wire or RF needle.…”
Section: Discussionsupporting
confidence: 87%
“…Apart from imaging advancements, tools such as the use of purpose-built RF puncture technology have been shown to result in shorter instrumentation time, greater efficacy in transseptal crossing, and fewer episodes of pericardial tamponade [10]. More recently, the RF wire system was shown to achieve completely fluoroless transseptal puncture safely and effectively while improving procedural efficiency in RF ablations [11]. Several studies have shown the benefits of a steerable sheath for RF ablations [4,[12][13][14], however, the use of steerable sheath for transseptal puncture remains uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…The transseptal sheath is then replaced by a large bore sheath. Demo et al has recently demonstrated the feasibility and efficacy of this system in CBA procedures [18]. However, it is important to realize that with the VersaCross system, you still need to exchange the standard transseptal sheath for the large bore sheath; thus, it is not a zero-exchange approach like the AcQCross system.…”
Section: Discussionmentioning
confidence: 99%
“…special radiofrequency wires like VersaCross ® (Baylis Medical). 5 The introduction of radiofrequency catheters with force or local impedance sensors and algorithms for lesion formation assessment have led to shorter radiofrequency application times, and along with secondgeneration single-shot cryoballoon ablation systems, have led to improved safety and a decrease in ablation procedure time. In addition, performing the procedures on continuous anticoagulation has proven to be safe and has led to lower periprocedural thromboembolic events.…”
mentioning
confidence: 99%
“…The adoption of ultrasound‐guided vascular access has led to a 2/3 decrease in procedural vascular complications 4 . Transseptal puncture, which many physicians consider one of the most dreaded steps of the procedure, has become safer under direct visualization guided by intracardiac echo and three‐dimensional mapping, using special radiofrequency wires like VersaCross® (Baylis Medical) 5 …”
mentioning
confidence: 99%